Dopplervelocimetria da artéria oftálmica em gestantes portadoras de lúpus eritematoso sistêmico sem atividade de doença renal - Freitas, Márcia Aires Rodrigues de (2009)
Purpose: To analyze the patterns of dopplervelocimetry of the ophthalmic artery in pregnant and no-pregnant patients with systemic lupus erythematosus (SLE) without renal disorder flares, and to compare the Doppler indexes of normal pregnant women. Methods: an observational study was carried out through Doppler indexes evaluation of the ophthalmic artery of 20 normal pregnant women, 10 pregnant women with SLE, and 17 non-pregnant women with SLE. The variables analyzed were: pusatility and resitance indexes (PI, RI), peaks systolic velocity, and the enddiastolic flow velocity (PSV, EDV) and peak ratio (PR). For the comparison of the Doppler indices the test of variance (ANOVA) and the post-analysis test of Tukey were used. The Pearson linear correlation analysis was performed to study the values changes at the time of the disease. The level of significance determined in the study was 5%. Result: there were no significant differences between the two SLE groups, concerning the Doppler values, except for PSV (p=0,026). Nevertheless, the means of RI, PI, EDV and PR of the ophthalmic arteries were compared, between the groups of normal pregnant women and pregnant women with SLE, significant differences were observed (p=0,01; p=0,02; p=0,05; p=0,04) The RI and PI, in both groups of women with ESL, were lower them the indexes of normal pregnants. But PR and EDF were higher in women with ESL whem compared with normal pregnants. There were no signiticant correlation between time of lupus and Doppler indexes PI, RI, SVF, EDV, PR, for pregnant groups (r=0,509, r=0,462;r=0,738;r=0,422) and non-pregnants (r=0,840; r=0,005; r=0,063; r=0,284; r=0,323). Conclusions: There was ophthalmic artery impedance flow reduction in both groups of patients with SLE compared to normal pregnants. Concerning the Doppler variables of the ophthalmic arteries, there were no significant differences between the groups of pregnant and non-pregnant women with SLE. No association of time of disease and ophthalmic artery Doppler indexes , in both pregnants groups, was found.